This World is Ours! - Petaja, Emil, 1915-2000 (Salt Lake City, UT : Project Gutenberg, 2021)
"This World is Ours!" by Emil Petaja is a science fiction novel likely written in the early to mid-20th century. The narrative revolves around themes of alien influence and manipulation, specifically focusing on a character embroiled in the world of science fiction publishing who uncovers a dark secret about extraterrestrial beings known as the Kiriki that pose a threat to humanity. The story follows Max Field, a science fiction writer who becomes embroiled in a peculiar and dangerous situation with his enigmatic editor, Wallace Starr. As Max works for the science fiction magazine "Orion," he begins to suspect that Starr is not human but rather a member of the alien Kiriki species, intent on spreading a cosmic agenda of control through their stories. The tension escalates when Max realizes that his new romantic interest, Alice, might also be part of this alien scheme. In a thrilling climax, Max, alongside another writer, Ric Planter, ultimately confronts and overcomes the Kiriki threat through a clever use of insecticide, deciding to launch a counter-narrative to preserve humanity against future invasions. The novel expertly blends elements of suspense and satire, exploring the intersection of fiction and reality while leaving readers pondering the nature of manipulation in storytelling. (This is an automatically generated summary.)
Release date is 2021-07-19
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Human-alien encounters -- Fiction; Science fiction -- Authorship -- Fiction